Psychopersonal characteristics of women with varying degrees of menopausal disorders - N.S. Lutsenko; O.D. Mazur; O.S. Shapoval; L.I. Zvarich; N.F. Efimenko (Сучасні медичні технології)
The perimenopausal period is the age of the highest spiritual and intellectual development of a woman; therefore, neurovegetative and psycho-emotional disorders of this period acquire a pecial medical and social value and require an interdisciplinary approach.